2012
DOI: 10.1111/j.1743-6109.2011.02517.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexual Dysfunction Among Postmenopausal Women with and Without Metabolic Syndrome

Abstract: Introduction The metabolic syndrome (MetS) is a multifactorial disease characterized by the co-occurrence of impaired glucose tolerance/diabetes, central obesity, high levels of triglycerides, low levels of high-density lipoprotein, and hypertension. Its prevalence is higher in menopausal women. We, and others, have recently shown that female sexual dysfunction (FSD) affects menopausal women. Whether the presence of MetS may be linked to a higher risk of FSD in menopausal women is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 58 publications
5
72
0
9
Order By: Relevance
“…(10) who evaluated the occurrence of FSD in postmenopausal women using the FSFI questionnaire. These authors found a prevalence of FSD of 68% in patients with MS, compared with 41% in those without MS. Based on that, we estimated in our study a sample size of 200 women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) who evaluated the occurrence of FSD in postmenopausal women using the FSFI questionnaire. These authors found a prevalence of FSD of 68% in patients with MS, compared with 41% in those without MS. Based on that, we estimated in our study a sample size of 200 women.…”
Section: Methodsmentioning
confidence: 99%
“…Decreases in FSFI total scores were proportional to an increase in the number of MS components (9). Another study in postmenopausal women also found an association between MS and low sexual function scores (10). In contrast, Kim and cols., while studying middleaged women, found no association between MS and most of the components of sexual function (11).…”
mentioning
confidence: 89%
“…Los factores asociados a la disfunción sexual han sido estudiados por varios autores, registrando el síndrome metabólico como un factor de riesgo independiente (16)(17)(18), la edad, el grado de instrucción, la salud física (19,20) y mental en la mujer (21), aunque otros autores refieren además el estado civil casado, hábito de fumar (22), así como tener más de 14 años de matrimonio, más de 2 hijos, el grado de instrucción, el tener una pareja mayor de 42 años (23) y el uso de terapia antidepresiva (24).…”
Section: Introductionunclassified
“…9 Another metabolic syndrome that was suggested to increase the prevalence of FSD is the high levels of triglycerides. 10 Smoking, alcohol consumption, and physical activitiies are three among examples of habits and life style that allegedly influence prevalence of FSD in menopausal women. Smoke for example may cause early onset of menopause and high incidence of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%